Structural Equation Modeling of Airlines Service Quality: A Study of Airlines Industry in India - Kumar, Anoop; Malik, Gunjan (Prabandhan: Indian Journal of Management, 2022)
Providing quality service is an integral part of any airline’s efforts to increase profitability and cope with the growing aggressive competition that has emerged after the deregulation. To do this, the airlines must understand the requirements of their passengers and try to meet their expectations. This study tried to develop a scale consisting of the dimensions of service quality in the domestic airline industry in India, which has been experiencing a boom owing to the increasing number of passengers traveling by air. An extensive literature review was done, followed by empirical research conducted with the help of 384 questionnaires consisting of 28 items. The validity and reliability of the items were checked with KMO’s Bartlett’s test. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used for the study. The research established five dimensions of service quality known as EATRC (i.e., Employees, Assurance, Tangibles, Reliability, and Check-in) along with 23 sub-dimensions that depicted passengers’ perception of service quality. CFA was used to confirm the overall fitness of the model and validate the hypothesized relationships.